Net Neutrality and the Battle for the Open Internet - Kimball, Danny, 1983-; Project Muse. (Ann Arbor : University of Michigan Press, 2022)
""Net neutrality," a dry but crucial standard of openness in network access, began as a technical principle informing obscure policy debates but became the flashpoint for an all-out political battle for the future of communications and culture. Net Neutrality and the Struggle for the Open Internet is a critical cultural history of net neutrality that reveals how this intentionally "boring" world of internet infrastructure and regulation hides a fascinating and pivotal sphere of power, with lessons for communication and media scholars, activists, and anyone interested in technology and politics. While previous studies and academic discussions of net neutrality have been dominated by legal, economic, and technical perspectives, Net Neutrality and the Struggle for the Open Internet offers a humanities-based critical theoretical approach to net neutrality, telling the story of how activists and millions of everyday people, online and in the streets, were able to challenge the power of the phone and cable corporations that historically dominated communications policy-making to advance equality and justice in media and technology"--
Introduction: the broadband battle -- Democratic communications infrastructure, discourse, policy, and advocacy -- Defining broadband -- Clash of titans or the best of frenemies? -- Nuclear net neutrality -- The Title II turn -- Organizing for net neutrality -- Conclusion: boring points.
Description based on print version record.
Keywords: Political activists; Internet service providers; Internet and activism; LAW / Computer & Internet; SOCIAL SCIENCE / Media Studies; Political activists; Internet service providers; Internet -- Access control -- Social aspects; Internet and activism; Network neutrality -- Social aspects; Electronic books